VARICOCELE EMBOLIZATION FOLLOWING FAILURE OF VARICOCELECTOMY: A CASE SERIES AND REVIEW OF LITERATURE - Badar, Zain; Rachun, Michael; Farooq, Zerwa; Calabrese, Megan; Mohamed, Anthony; Jawed, Mohammed (Journal of Ayub Medical College Abbottabad, 2016)
Varicocelectomy remains the same mainstay of treatment for varicoceles. However with growing focus on minimally invasive techniques, recent literature has investigated the use of venous embolization for the treatment of varicoceles in patients with recurrence after surgical treatment. Embolization has many advantages, including use of local anesthesia, lower operating time, decreased risk of hydrocele and faster recovery times. In addition to this direct visualization of the vasculature during embolization allows for identification of any anatomic variants or collateral vessel accounting for the recurrence. This permits more definitive treatment in case of prior surgical failure. We present a case series where venous embolization is successfully done following failure of varicoclectomy. For patients who experience recurrence after a varicocelectomy, we recommend consideration for varicocele embolization. Varicocelectomy remains the same mainstay of treatment for varicoceles. However, with growing focus on minimally invasive techniques, recent literature has investigated the use of venous embolization for the treatment of varicoceles in patients with recurrence after surgical treatment. Embolization has many advantages, including use of local anaesthesia, lower operating time, decreased risk of hydrocele and faster recovery times. In addition to this direct visualization of the vasculature during embolization allows for identification of any anatomic variants or collateral vessel accounting for the recurrence. This permits more definitive treatment in case of prior surgical failure. We present a case series where venous embolization is successfully done following failure of varicocelectomy. For patients who experience recurrence after a varicocelectomy, we recommend consideration for varicocele embolization. Keywords: Varicocelectomy; Varicocele embolization; Recurrence